2011
DOI: 10.1002/anie.201104858
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Component Coupling of Arynes and Organic Bromides

Abstract: Magic trio: Arynes are easily coupled with neutral nucleophiles and organic bromides to afford functionalized bromoarenes depending upon the nucleophile (Nu). The three‐component coupling proceeds through the formation of bromine ate complexes, and can be applied to the synthesis of multisubstituted isoquinolines and benzo[b]oxepines having pharmacological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(36 citation statements)
references
References 44 publications
(13 reference statements)
1
34
0
1
Order By: Relevance
“…4c In addition, pyridine and 1,2,3-triazole N -oxides undergo oxidative C2–H and C5–H homocoupling reactions, respectively. 10 …”
mentioning
confidence: 99%
“…4c In addition, pyridine and 1,2,3-triazole N -oxides undergo oxidative C2–H and C5–H homocoupling reactions, respectively. 10 …”
mentioning
confidence: 99%
“…Isocyanide-derived zwitterion 82 can also be captured by alkynyl and perfluoroaryl bromides to give 84 and 85 (Scheme 73), 228 and the method allows the use of cyclic ethers including oxetanes and THF of less nucleophilicity, which are transformed into ring-opened products (Scheme 74). C-Br bond-and subsequent C-C bond-forming processes between carbanion 86 and nitrilium cation 87 (or oxonium cation 88) rationally explain the product formation (Scheme 75).…”
Section: Tmsmentioning
confidence: 99%
“…However, Takaki and coworkers reported that a dipolar adduct of an isocyanide to a benzyne could abstract the bromine to produce a C 6 F 5 − anion that will add to the nitrilium to form an imine (eq 11). 15 Gevorgyan reported that an enolate can abstract Br + from C 6 F 5 Br to produce an α-bromoketone and a C 6 F 5 − anion. The nucleophilic addition of the latter at the carbonyl group generates an alkoxide, which, upon intramolecular S N 2 reaction, provides a C 6 F 5 -substituted epoxide (eq 12).…”
Section: F 5 Brmentioning
confidence: 99%